Correction: Corrigendum: Whole genome analysis of a schistosomiasis-transmitting freshwater snail - Coen M. Adema (Nature Portfolio, 2017)
Nature Communications 8: Article number: 15451 (2017); Published 16 May 2017; Updated 23 August 2017 The original version of this Article contained an error in the spelling of the author Leon Di Stefano, which was incorrectly given as Leon di Stephano. This has now been corrected in both the PDF andHTML versions of the Article.